Narrowband Ultraviolet B (NB-UVB) Phototherapy in Psoriasis: A Retrospective Study - Prameswari, Faida Ufaira; Cita Rosita Sigit Prakoeswa; Ferriastuti, Widiana (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Psoriasis with higher Psoriasis Area and Severity Index (PASI) scores correlate with impaired quality of life. Assessing narrowband ultraviolet B (NB-UVB) phototherapy as a new therapy option in Indonesia is necessary to find the most effective treatment for psoriasis patients. Purpose: To determine the usage of NB-UVB phototherapy and the therapy response in psoriasis patients. Methods: This retrospective descriptive observational study was conducted at Dr. Soetomo General Academic Hospital Surabaya in March 2019-November 2020. The variables were collected through medical records. Result: A total of 28 patients were obtained at this study. Psoriasis type plaque/vulgaris were found in 92.9% of the patients. The patients mostly started with PASI score >10 with the initial dose of NB-UVB phototherapy is 260 mJ/cm2. The most common initial phototherapy frequency is 3 times per week (53.6%). The latest dose and frequency distribution was varied in each subject. The mean total number of sessions was 31.54 ± 20.549. Patients were also administered various combination therapy. The majority of patients had missed NB-UVB phototherapy sessions and the phototherapy dose needed to be reduced (57.1%). The achievement of PASI-75 (treatment success) was mostly achieved by subjects that went through 40-60 sessions of phototherapy and subjects with psoriasis type plaque/vulgaris. Conclusion: The achievement of PASI-75 was found to be low (17.5%), influenced by multiple factors such as the total number of NB-UVB phototherapy sessions, combination therapy, dose of NB-UVB phototherapy, frequency of NB-UVB phototherapy, and the level of patient compliance to therapy.